Tomato as a Natural Source of Dyes in the Food Industry: A Patent Data Analysis - de Lima Silva, Vanessa; Leite, Bruna S.; do Espírito Santo de Jesus, Fabiane; Martins, Lissa Daltro; Assunção, Larissa Santos; Leal, Ingrid Lessa; Colauto, Nelson Barros; Colauto, Giani Andrea Linde; Souza Machado, Bruna Aparecida; Ferreira Ribeiro, Camila Duarte (Recent Patents on Nanotechnology, 2023)
Background: Foods that promote health benefits are being increasingly used. Innovative techniques, such as nanotechnology, have been used to improve functional properties, sensory characteristics, or the conservation of foods. Objective: The objective of this study was to identify the technological domain of patents for tomato products with or without nanotechnology and elucidate the technological advances associated with the recent use of tomatoes as a natural food dye in the food industry by exploring patent documents. Methods and Results: The search was conducted using the Espacenet and INPI databases. There was an increase in patent document applications employing nanotechnology in 2013, with a peak between 2017 and 2018. China is the lead country in the number of patent applications. In Brazil, the patent applications are variable, and the food industry is most involved in studies on tomatoes as a natural food dye. Most patent deposits using nanotechnology were from companies, and the main sources of the patent application were the food and pharmaceutical industries. Conclusion: There is an increasing trend for the use of tomatoes as natural food dyes, produced with or without nanotechnology, and number of patents filed yearly. New technologies are being developed in several application areas.
Keywords: vitamin E